Paulus i Aristoteles’ hønsegård - Buch-Hansen, Gitte (Dansk Teologisk Tidsskrift, 2014)
In modern kinship, biology represents the norm and adoption the exception. But in Greek antiquity and in Roman Hellenism, we face a tension between the patrilinear ideology and the fact that only in the case of the mother, biological parenthood could be established. In order to make up for this ideological deficit, adoption came to be ranked higher than biology. Through rituals of sacrifice and cleansing, the child was separated from the mother, adopted by the father and incorporated into his lineage. However, Second Temple Judaism represents an exception to this tradition. Apparently, being of Abraham’s seed was too strong an identity marker to be dispensed with. The article demonstrates how Paul – as the apostle to the Gentiles – navigates between Jewish genealogy and Hellenistic ideas about generation. The solution to Paul’s predicament is found in 1 Cor 15:45: as spiritualized body, Christ has literally become Abraham’s seed. Thus, through their reception of Christ’s spirit in baptism, believers are incorporated into the Abrahamic lineage. But in order to understand the ethnic reconfiguration which takes place in Pauline baptism, we must have recourse to Aristotle’s reflections on poultry farming in his treatise, De Generatione Animalium.